EP622 Use of pelvic lymphadenectomy in the management of high grade & type 2 endometrial cancer: a survey of current practice of gynaecological oncology centres in the united kingdom. (1st November 2019) - Jones, R; Howells, R; Lim, K; Sharma, A
Abstract : Introduction/Background: Previous trials have not shown any therapeutic benefit of pelvic lymphadenectomy (PL) in high grade or type 2 endometrial cancer but doubts have been raised regarding the findings of these trials due to their methodology. The recent ESGO guidelines (2016) have only recommended lymphadenectomy for purpose of comprehensive staging and determining prognosis. Our aim was to assess the current practice of gynaecological oncology centres in the United Kingdom. Methodology: We surveyed the membership of the British Gynaecological Cancer Society (BGCS) via an online survey platform from 01/11/2017–30/06/2018. A single reminder was sent during the collection period. Information was gathered regarding type of surgery offered, proportion of procedures completed through minimally invasive surgery, whether PL is offered routinely and what adjuvant treatment is offered. Data analysis was with Microsoft Excel. Results: Responses were received from 17 of the 33 (52%) UK gynaecological oncology centres. All centres reported offering hysterectomy and bilateral salpingo-oophorectomy as the main treatment. Omental biopsy or omentectomy was reported as offered in 4 (24%) centres for high grade and 100% of centres for type 2 disease. 12 (71%) centres reported >75% of cases were completed through a minimally invasive procedure, the remaining 5 (29%) centres reported 50–75% of cases being completed minimally invasively. 15 (88%) centres reported offering PL routinely, 10 of these provided complete information regarding the adjuvant treatment offered, 9 of which reported altering the adjuvant therapy offered dependent on whether PL had been undertaken or not. Conclusion: Although there is variation in the procedures performed, most of the responding centres performed surgical assessment of pelvic lymph nodes; the majority of these report using it to guide what adjuvant therapy is offered. Further prospective trials are required to assess the value of PL in management of high grade and Type 2 endometrial cancers. Disclosure: Nothing to disclose.